Papert’s Microworld and Geogebra: A Proposal for Enhancing Functional Teaching - Carlos Vitor De Alencar Carvalho; Lícia Giesta Ferreira De Medeiros; Antonio Paulo Muccillo De Medeiros; Ricardo Marinho Santos (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
This paper discusses how to improve teaching of Mathematics in Brazilian schools, based on Seymour Papert’s Constructionism associated with Information Technology tools. Specifically, this work introduces the constructionist microworld, a digital environment where students are able to build their knowledge interactively, in this case, using dynamic mathematics software GeoGebra. Papert’s constructionism offers a versatile framework to implement pedagogical models using computers.